Novel Method for the Growth of Two-Dimensional Layered InSe Thin Films on Amorphous Substrate by Molecular Beam Epitaxy - Hsiao, Sheng-Wei; Yang, Chu-Shou; Yang, Hao-Ning; Wu, Chia-Hsing; Wu, Ssu-Kuan; Chang, Li-Yun; Ho, Yen-Teng; Chang, Shu-Jui; Chou, Wu-Ching (Frontiers in Materials, 2022)
A two-dimensional (2D) material known as indium selenide (InSe) is widely considered a promising layered semiconductor with potential applications in electronics and optoelectronics. However, the single phase of InSe is still a challenge due to the close formation energy of InSe and In2Se3. In this study, we demonstrate a novel growth method for 2D InSe with an indium precursor layer by molecular beam epitaxy. Indium pre-deposited on substrate at room temperature followed by growth of InSe at 550°C can overcome the problem of stoichiometry control and can be applied on amorphous substrates with high quality. According to Raman scattering spectra, X-ray diffraction, and high-resolution transmission electron microscopy results, we find that 2D InSe phase can be facile formed under both indium-rich and -poor conditions. The pre-deposited indium precursor effectively induces replacement with subsequent Se and In atoms to form the InSe phase while suppressing the In2Se3 phase. Additionally, this single phase InSe is stable in the atmosphere, exhibiting superior electronic properties even after over 100 days of exposure. Recently, this method has been successfully applied to a flexible substrate, such as aluminum foil, resulting in reliable InSe quality. Our results demonstrate an innovative and forward-looking approach to developing 2D InSe material.